The Intervening Role of Value Added Intellectual Capital on The Relationship between Corporate Governance and Firm Value - Saarce Elsye Hatane; Melinda Setiadi; Josua Tarigan (Journal of Accounting and Investment, 2019)
The purpose of this research is to analyze the direct impact of board structures on intellectual capital and firm value. The intellectual capital has a role as the mediating variable between corporate governance and firm value. Corporate governance is indicated by board size, gender diversity, and managerial ownership. Intellectual capital and firm value are measured by VAICTM and Tobin’s Q approximation respectively. Specifically, this study is conducted in the consumer goods sector during 2010-2015 in Indonesia and Malaysia. Total samples gathered from Indonesia Stock Exchange and Bursa Malaysia are 25 Indonesia companies (150 firm-year) and 106 Malaysia companies (636 firm-year). Partial least square is applied in order to examine the research model. The findings support all the proposed hypothesis, that corporate governance in both Indonesia and Malaysia have a positive significant impact on intellectual capital and value. In both countries, intellectual capital also has a positive significant impact. However, the main driver of significance on intellectual capital is different. Furthermore, intellectual capital in Malaysia is successfully intervening in the relationship between board structures and firm value